The Flood and Kant’s Epistemology against Man’s Alienation in Wallace Stevens’ “The Comedian”: The Flood and Kant’s Epistemology against Man’s Alienation in Wallace Stevens’ “The Comedian” - Benmezal, Farid (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2024)
This article examines the connectedness between Wallace Stevens’ idea of a balance between reality and the imagination in his poem “The Comedian as the Letter C” and Kant’s idea that man’s knowledge of the world is always mediated by mental representations. Aware that the decline of spirituality means that man is left alienated in a thoroughly material world, Stevens strives to rescue humanity from spiritual emptiness and to make out of the same reality poetry in which the imagination brings meaning to man’s existence. In this poem, Stevens makes use of the motif of the flood as an intertextual response to Hegel’s reading of the Greek and biblical stories of the flood that places Kant in the biblical tradition in which man’s submission to God leads to his severance from his reality while the Greek story emphasizes the harmonious coexistence between man and nature. Owing to the nature of this study, this article relies on close reading, a technique advocated by the New Critics and Julia Kristiva’s intertextuality that insists on the presence of elements of one text within another. This methodology highlights that the flood in “Comedian” is a vehicle through which Stevens rejects Hegel’s anti-Kantianism and insists that Kant’s epistemology is the most suitable philosophical paradigm to create a union between man and nature in a secular age. This union is possible if the poet is able to reach a balance between reality and the imagination.